NILAI KESETARAAN LAHAN BUDI DAYA TUMPANG SARI TANAMAN TEBU DENGAN KEDELAI: STUDI KASUS DI DESA KARANGHARJO, KECAMATAN SULANG, KABUPATEN REMBANG - Ahmad Rifai; Seno Basuki; Budi Utomo (Pusbindiklat - LIPI, 2014)
Self-sufficiency of soybeans and sugar is one of main targets of the Ministry of Agriculture’s strategic plan in 2014. This government’s target may not be achieved due to the lack of land for cultivation. This research aims to analyze the efficiency of land use by using monoculture and intercropping methods for growing sugarcane and soybean. The results of experiment studies showed that the Land Equivalent Ratio (LER) between sugarcane and soybean has a value greater than 1in overall, indicating that the intercropping pattern is more efficient and productive than the monocultures cropping. The highest LER is VMC76-16+Kaba varieties intercropped, which is 2.21, while the lowest LER is intercropped PSJK922+Argomulyo, which is 1.41. Based on financial analysis, the highest NPV is Rp126,852,727,00, the B/C ratio is 2.56 for intercropping of VMC 76-16 + Argomulyo. Based on these results, the area of 64501.99 ha sugarcane in Central Java can potentially increase the soybean area 32250.995 ha and its production 56,700 tons per year.